2020
DOI: 10.1038/s41598-020-67383-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of occlusal splint on oxidative stress markers and psychological aspects of chronic temporomandibular pain: a randomized controlled trial

Abstract: have their natural teeth and maintain good oral hygiene. Participants were not suitable if they were experiencing (1) inflammatory joint disease, (2) orofacial pain unrelated to TMD, (3) chronic systemic diseases (i.e. diabetes, cardiovascular diseases, malignancies, and autoimmune diseases), (4) causes of headache, unrelated to TMD, listed in the International Classification of Headache Disorders (ICDH II), (5) periodontitis, oral lesions and gum swelling. Individuals who had already been under treatment for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…There was a report of no improvement with the use of occlusal splints. without cognitive therapy [59], and reports of improvement with hard and soft splints [64,65]. Piancino et al [60] and Miralles et al [51] showed improvement in the pattern of movement of the SS, with positive influence on the cervical spine, respectively, when using JFO, corroborating the findings of the present investigation.…”
Section: Discussionsupporting
confidence: 90%
“…There was a report of no improvement with the use of occlusal splints. without cognitive therapy [59], and reports of improvement with hard and soft splints [64,65]. Piancino et al [60] and Miralles et al [51] showed improvement in the pattern of movement of the SS, with positive influence on the cervical spine, respectively, when using JFO, corroborating the findings of the present investigation.…”
Section: Discussionsupporting
confidence: 90%
“…They were given only basic information about the nature of the diagnosis and the therapeutic device assigned to them. The design of the device was explained in our previous research 24 . All contacts that interfered with simultaneous contact at maximum intercuspation were removed, allowing the vertical dimension of the occlusion to increase by <0.5 mm which we considered as negligible effect on occlusion and condyle position.…”
Section: Methodsmentioning
confidence: 99%
“…The design of the device was explained in our previous research. 24 All contacts that interfered with simultaneous contact at maximum intercuspation were removed, allowing the vertical dimension of the occlusion to increase by <0.5 mm which we considered as negligible effect on occlusion and condyle position. Participants were instructed to wear the device only during sleep.…”
Section: Control Therapymentioning
confidence: 99%
“…PHQ-9 is a nine-item questionnaire designed to screen for depression with responses based on a four-point Likert scale (from not at all to almost every day) with possible scores from 0 to 27 (Alajbeg et al, 2020). GAD-7 is a seven-item questionnaire used to assess the severity of anxiety symptoms with responses based on a Likert scale (from not at all to almost every day) with possible scores from 0 to 21 (Gikić et al, 2021).…”
Section: Diagnosis Of Temporomandibular Disordersmentioning
confidence: 99%